Zabezpieczenie społeczne ryzyka starości w ustawie o pomocy społecznej - Lewandowicz-Machnikowska, Monika (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The paper discusses protection against risks related to old age, which is provided by the Polish social security law other than national social insurance law, namely by the Social Assistance Act. It describes prerequisites for being granted the right to permanent benefit, which apply to people with work disability due to age. The author analyses in particular at what age, under the law, a person is considered to be incapable of work. She examines whether the regulations on permanent benefits implement the civil right to social security as provided by Article 67 of the Constitution of the Republic of Poland. In the author’s view, the permanent benefit may be developed in the future into a new system of social security, not based on the insurance model — the civic pension.
Keywords: zabezpieczenie społeczne; ustawa o pomocy społecznej; starość; ryzyko